Assessment of the influence of examination postures on postural stability by means of the DTP-3 diagnostic system [Hodnocení vlivu vyšetřovacích poloh na posturální stabilitu pomocí diagnostického systému DTP-3] - Peter D. C. Phiri; Jakub Krejčí; Jiří Salinger (Palacky University, 2009)
BACKGROUND: When examining spinal shape by means of radiographic methods, as well as non radiographic non invasive methods, standardisation of the examined person's posture is essential. OBJECTIVE: Standardizing examination posture serves to enable the mutual comparison of the results from examinations when performed using different methods. Furthermore, a suitable examination posture should reduce postural sway and thus increase the reliability of such an examination. METHODS: For the purpose of assessing the influence of fixation on reducing postural sway in a subject undergoing an examination, two examination postures with different degrees of fixation were proposed: posture D - a standing position with shoulders supported against a fixation frame and posture F - prone lying on a fixation bed. Those postures were compared with posture A - the free standing position. For the examination of spinal shape and postural stability, the DTP-3 microcomputer diagnostic system was used, which makes it possible to measure a three-dimensional position of points by applying a non invasive contact method. The examination consists of palpating and marking the skin projection of the left and right lateral parts of the acromion, bilateral posterior superior iliac spine, and the processus spinosi. The marked points are scanned by touching them with the position sensor stylus and transmitted into a computer, where they are displayed as output protocols in the form of tables and graphs. The experimental part included the measurement of 80 subjects (40 men and 40 women, aged 23.1 ± 2.5 years). Each subject was measured five times in each examination posture, and the average spinal curve was calculated, as well as the standard deviation, evaluating the postural sway of the examined subject. RESULTS: It results from the assessment of the effects of fixation on postural sway reduction, which increased fixation in examination postures A-D-F results to postural sway reduction, expressed by means of standard deviations in the mediolateral direction: 3.63-1.12-0.86 [mm], in the posterioanterior direction: 5.25-2.94-1.33 [mm] and in the caudocranial direction: 1.30-1.33-1.00 [mm]. It further results from the assessment that postures D and F significantly reduce postural sway towards posture A and posture F further reduces postural sway towards posture D. [VÝCHODISKA: Při vyšetřování tvaru páteře jak rentgenologickými, tak neradiačními neinvazivními metodami je důležitá standardizace polohy vyšetřované osoby. CÍLE: Standardizace vyšetřovací polohy umožní vzájemné porovnání výsledků vyšetření různými metodami. Navíc vhodná vyšetřovací poloha by měla snížit titubaci a tím zvýšit reliabilitu vyšetření. METODIKA: Pro hodnocení vlivu fixace na snížení titubace vyšetřované osoby byly navrženy dvě vyšetřovací polohy s různým stupněm fixace: poloha D - stoj s oporou ramen o fixační rám a poloha F - leh na břiše na fixačním lůžku. Uvedené polohy byly porovnány s polohou A - volný návykový stoj. Pro vyšetření tvaru páteře a titubace byl využit mikropočítačový diagnostický systém DTP-3, který umožňuje měřit třírozměrnou polohu bodů neinvazivní dotykovou metodou. Metodika vyšetření spočívá v palpaci a označení projekcí akromionů, zadních horních spin a trnových výběžků na kožním povrchu vyšetřované osoby. Označené body jsou snímány dotykem hrotu polohového snímače a přenášeny do osobního počítače, kde jsou zobrazeny do výstupních protokolů ve formě tabulek a grafů. Byl změřen soubor 80 vyšetřených osob (40 mužů a 40 žen, věk 23,1 ± 2,5 roku). Každá osoba byla v každé vyšetřovací poloze změřena pětkrát a byla vypočítána průměrná křivka páteře a standardní odchylka kvantifi kující titubaci vyšetřované osoby. VÝSLEDKY: Z hodnocení vlivu fixace na snížení titubace vyplývá, že rostoucí stupeň fixace vyšetřovacích poloh A-D-F vede ke snížení titubace vyjádřené pomocí průměrných hodnot standardních odchylek v mediolaterálním směru: 3,63-1,12-0,86 [mm], v posterioanteriorním směru: 5,25-2,94-1,33 [mm] a ve kaudokraniálním směru: 1,30-1,33-1,00 [mm]. Z hodnocení dále vyplývá, že polohy D a F významně snižují titubaci vůči poloze A a poloha F dále snižuje titubaci vůči poloze D.]